2010
DOI: 10.1111/j.1469-8986.2009.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emotion on respiratory-related evoked potentials

Abstract: Emotion influences the perception of respiratory sensations, although the specific mechanism underlying this modulation is not yet clear. We examined the impact of viewing pleasant, neutral, and unpleasant affective pictures on the respiratory-related evoked potential (RREP) elicited by a short inspiratory occlusion in healthy volunteers. Reduced P3 amplitude of the RREP was found for respiratory probes presented when viewing pleasant or unpleasant series, when compared to those presented during the neutral se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 72 publications
9
38
1
1
Order By: Relevance
“…The RREP is directly related to respiratory sensory perception in healthy subjects and in life-threatening asthma patients (Davenport et al, , 2000Knafelc and Davenport, 1999). Emotion does not modify the amplitudes of the RREP early peaks (von Leupoldt et al, 2010b) suggesting that affect does not act on respiratory perception by increasing the respiratory sensory-related discriminative cortical activity.…”
Section: Introductionmentioning
confidence: 98%
“…The RREP is directly related to respiratory sensory perception in healthy subjects and in life-threatening asthma patients (Davenport et al, , 2000Knafelc and Davenport, 1999). Emotion does not modify the amplitudes of the RREP early peaks (von Leupoldt et al, 2010b) suggesting that affect does not act on respiratory perception by increasing the respiratory sensory-related discriminative cortical activity.…”
Section: Introductionmentioning
confidence: 98%
“…Yuen et al [13] believe that the states of the brain change as feelings change, therefore, EEG is suitable for the task of recording the changes in brain waves, which vary according to feelings or emotions; a neural network was used to train the model. Leupoldt A et al [14] observed the emotion influence on respiration sensation, skin conductance response and EEG. Kreibig [3] conducted a survey of several research studies to find the relationship between autonomic nervous system (ANS) and the human emotions.…”
Section: Related Workmentioning
confidence: 99%
“…Within the brain, it appears that the middle insula integrates afferent interoceptive information with exteroceptive context into broader motivational space, but individuals differ in the degree to which such information propagates to the prefrontal cortex, and presumably conscious awareness, as a function of interoceptive practice (Singer et al, 2009;Farb et al, 2012b). In addition to neuroimaging, it should be noted that many other psychophysiological indicators of interoceptive processing show promise for revealing interoceptive processing in the absence of participant report, such as heartbeat-evoked potentials (Leopold and Schandry, 2001), respiratory-related potentials (Von Leupoldt et al, 2010), cardiac modulation of startle (Schulz et al, 2009), or EEG-ECG single trial covariation (Mueller et al, 2013). For example, Von Leupoldt et al (2010) demonstrated that respiratory occlusion produced a reliable respiratory-related evoked potential measurable by EEG, which serves as an index of cortical tracking of interoceptive signals.…”
Section: Regulation Through Simulationmentioning
confidence: 99%
“…In addition to neuroimaging, it should be noted that many other psychophysiological indicators of interoceptive processing show promise for revealing interoceptive processing in the absence of participant report, such as heartbeat-evoked potentials (Leopold and Schandry, 2001), respiratory-related potentials (Von Leupoldt et al, 2010), cardiac modulation of startle (Schulz et al, 2009), or EEG-ECG single trial covariation (Mueller et al, 2013). For example, Von Leupoldt et al (2010) demonstrated that respiratory occlusion produced a reliable respiratory-related evoked potential measurable by EEG, which serves as an index of cortical tracking of interoceptive signals. Mueller et al (2013) indexed interoceptive processing by the degree to which EEG responses to task feedback predicted subsequent heartbeat acceleration.…”
Section: Regulation Through Simulationmentioning
confidence: 99%